2006
DOI: 10.5507/bp.2006.047
|View full text |Cite
|
Sign up to set email alerts
|

Bifocal pacing - A novel cardiac resynchronization therapy? Results of bifocal pacing study and review of the current literature

Abstract: Background: Bifocal pacing (BFP) has been proposed as a more feasible alternative of cardiac resynchronization therapy (CRT).Aim: To evaluate BFP in patients with severe congestive heart failure and significant intraventricular conduction delay and to compare it with biventricular pacing (BVP).Methods: Both echocardiographic examination including tissue Doppler imaging and invasive measurements of cardiac hemodynamics was performed under basal conditions and during BFP and BVP.Results: 50 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(10 reference statements)
0
2
0
2
Order By: Relevance
“…I když je BiF výhodnější než klasická hrotová stimulace, nemá takový hemodynamický účinek jako BiV. 23 Předpokladem uplatnění BiV stimulace je, že excitujeme svalovinu laterální stěny, která musí být viabilní. V našem případě byl pacient po opakovaných infarktech v povodí RIA.…”
Section: Obrázek 6 Ekg Křivka Při Biventrikulární Stimulaciunclassified
“…I když je BiF výhodnější než klasická hrotová stimulace, nemá takový hemodynamický účinek jako BiV. 23 Předpokladem uplatnění BiV stimulace je, že excitujeme svalovinu laterální stěny, která musí být viabilní. V našem případě byl pacient po opakovaných infarktech v povodí RIA.…”
Section: Obrázek 6 Ekg Křivka Při Biventrikulární Stimulaciunclassified
“…Data from published acute studies (second site in the right ventricular (RV) outflow tract or on the interventricular septum) in CRT candidates suggest that BiF provides better acute hemodynamic performance than RV apical pacing but less pronounced hemodynamic improvement than biventricular pacing (Table I). 5–9 Although acute hemodynamic improvement with BiF has not yet been shown to translate into long‐term improvement in LV function, acute studies are encouraging and provide insight into the effects of BiF pacing. Using tissue Doppler‐imaging‐strain echocardiography, Matsushita et al 5 and Martiniello et al 6 have shown that BiF pacing is effective in reducing LV dyssynchrony.…”
Section: Acute Bifocal Right Ventricular Alternative Pacingmentioning
confidence: 99%
“…In an invasive hemodynamic investigation of 48 patients Van Campen et al 7 found a cardiac index of 1.94 during biventricular pacing and 1.90 during BiF pacing compared with 1.75 at baseline (P < 0.001). Bulava and Lukl 8 showed that biventricular pacing is more effective than BiF pacing in improving LV hemodynamics—expressed in terms of (invasive) LV dP/dt max , and echocardiographic evidence of LV resynchronization. In addition, in patients with nonischemic cardiomyopathy, the improvement of LV contractility with BiF pacing seemed to be directly correlated with the distance between RV apical and RV septal pacing sites.…”
Section: Acute Bifocal Right Ventricular Alternative Pacingmentioning
confidence: 99%
“…Ενώ στη δεύτερη, πέραν των τεχνικών δυσκολιών, που μπορούν να προκύψουν, ο ασθενής αντιμετωπίζει τον κίνδυνο θρομβοεμβολικών επεισοδίων και έχει ανάγκη αντιπηκτικής αγωγής εφ΄όρου ζωής, με όλους τους κινδύνους που αυτή εγκυμονεί.. Η ταυτόχρονη βηματοδότηση από δύο θέσεις της δεξιάς κοιλίας (κορυφή και χώρο εξόδου), σε σχέση με τη συμβατική βηματοδότηση από την κορυφή της δεξιάς κοιλίας, πιθανώς προκαλεί ταχύτερη διέγερση της αριστερής κοιλίας και επομένως αναμένεται να έχει σαν αποτέλεσμα την ομογενοποίηση της συστολής. [130,131] Η μέθοδος αυτή, έχει προταθεί σαν πιθανή εναλλακτική προσέγγιση στη ΘΚΕ. Οι Buckingham Et al., αναφέρουν βελτίωση του +dp/dt της αριστερής κοιλίας κατά την διεστιακή DVI βημαδότηση από τη δεξιά κοιλία σε ασθενείς με πτωχή λειτουργικότητα (ΚΕ<40%), ωστόσο οι ασθενείς της μελέτης αυτής είχαν εύρος QRS<120ms, επομένως η πιθανότητα ύπαρξης κοιλιακού δυσυγχρονισμού ήταν ελάχιστη.…”
Section: αποτελέσματαunclassified